Agricultural Development Banks: Close them or reform them? - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
Agricultural development banks were established to extend credit and other financial services to customers considered noncreditworthy by the commercial banking sector. Although frequently unprofitable, they play an important role in the fight against rural poverty. This article asks if these banks should be closed or if they are worth revamping.
Keywords: 330